Dinâmicas e transformaç\~oes territoriais recentes: O papel da PNDR e das políticas públicas n\~ao regionais com impacto territorial - Carlos Antônio Brand\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This study aims to present a systematic identification of themes and questions related to economic, social and demographic transformations in operation on national territory in the 2003-2015 period. A balance of efforts, advances and difficulties to implement the national regional policy (PNDR) is developed in order to subsidize the assessment process of regional policies in Brazil.
Keywords: O2; R5; R58; 330; regional development; regional policies; public policies